Pseudomonas aeruginosa Coharboring BlaKPC-2 and BlaVIM-2 Carbapenemase Genes - Tatiana Pacheco; Rosa Helena Bustos-Cruz; Deisy Abril; Sara Arias; Lina Uribe; Jenny Rincón; Julio-Cesar García; Javier Escobar-Perez (MDPI AG, 2019)
Pseudomonas aeruginosa, a bacterium commonly isolated from hospital settings, exhibits intrinsic resistance to a number of antibiotics and can acquire resistance during antibiotic therapy. Resistance towards carbapenems is increasing due to its overuse in the treatment of infections caused by extended-spectrum β-lactamase (ESBL) producing organisms. Nonetheless, carbapenems are essential for the treatment of high-risk infections and are one of the remaining weapons in the fight against “extreme drug resistance” of Gram-negative/positive bacilli. Herein, we describe a case report of infections caused by P. aeruginosa strains that carry blaVIM-2 and blaKPC-2 carbapenemase genes simultaneously, identified in five patients who were admitted to a high complexity health institution in Colombia. Molecular characterization included PCR screening for blaKPC, blaGES, blaOXA-48, blaIMP, blaNDM, and blaVIM carbapenemase and other resistance genes as well as analysis of the genetic relationships by genome macro-restriction and Pulsed-Field Gel Electrophoresis (PFGE) separation. In conclusion, these infections represent a major challenge to public health due to the risk of the infection spreading compounded by the fact that limited treatment options are available, thereby increasing the risk of increased morbidity and mortality.